Bank fraud : using technology to combat losses - Subramanian, Revathi (Hoboken, New Jersey : Wiley, 2014)
"Capitalize on technology to halt bank fraudExamining the technology that is needed to combat bank fraud, Bank Fraud: Using Technology to Combat Losses equips corporate security and loss prevention managers with the necessary tools to determine an organization's unique technology needs. Looks at the technology needed to handle data intelligence Provides guidance to assess the technology necessary to battle fraud Features unique coverage of the history of fraud detection and prevention in banking Explores the challenges of fraud detection in a financial services environment; understanding corporate risk exposure; losses per assets; trending over time; benefits of technology Focusing on the financial crimes and insider frauds in operation nationally and internationally, Bank Fraud: Using Technology to Combat Losses arms fraud prevention professionals with authoritative guidance to detect and prevent such crimes in future"--
DISTINCT STAGES OF A DATA-DRIVEN FRAUD MANAGEMENT SYSTEM.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Banks and banking -- Security measures; Bank fraud -- Prevention; Bank fraud -- Prevention -- Technological innovation; Bank fraud; Banks and banking; Commercial crimes; White collar crimes; BUSINESS & ECONOMICS -- Finance; Electronic books